Phytosanitary safety of agrocenoses of winter rape in Ukraine under the conditions of climate change - Borzykh, O.; Chaika, V.; Bublyk, L.; Bakhmut, O.; Shevchuk, O.; Kruk, I.; Fedorenko, A.; Gavrylyuk, L.; Vlasova, O.; Makovetskyi , Yu. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To analyze the multi-year population dynamics of the main pests of winter rape (Brassica napus L.) in different soil-climate zones of Ukraine in order to determine the impact of climate changes on the phytosanitary state of agrocenoses in 2012—2022. Methods. Analytical-synthetic method and computer modeling were used in the research. The results of monitoring of the development and spread of pests in agrocenoses of winter rapeseed and the forecast of their phytosanitary status during 2012—2022 were used as initial data. The long-term database of the Hydrometeorological Center of Ukraine was used to analyze the course of natural warming. The sums of effective temperatures for the development of insects were calculated for each soil-climate zone of Ukraine. Results. Ecological and statistical analysis of long-term data bases of winter rapeseed pest populations, dynamics of agrometeorological indicators was carried out. It was established that during 2012—2022, the sum of effective temperatures constantly exceeded the climatic norms in all soil-climate zones of Ukraine. There was a deterioration of heat and moisture supply during the growing season. As a result of climatic changes, the complex of pests is undergoing transformations. Conclusions. It has been established that as a result of climate changes, the area favorable for the cultivation of winter field crops, in particular winter rapeseed, is decreasing. The ability of the territory to self-cleaning falls. The long-term dynamics of the populations of the harmful entomocomplex of winter rape demonstrates a consistently high number of cruciferous fleas, rape flower beetle, rape stem borer and a tendency to increase the number of the latter. The crop is most vulnerable to phytophages in the seedling and budding-flowering phases, which must be taken into account when developing crop protection systems.